PENGARUH STRATEGI PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP FISIKA SISWA KELAS VIII SMP NEGERI 26 PEKANBARU - Famella, Wyrazona; Azhar, Azhar; Sahal, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aims to describe the influence of understanding concept physics students through the application of strategy problem based learning with conventional learning material optical instruments in class VIII SMP 26 Pekanbaru. The subjects were two class VIII SMP 26 Pekanbaru that homogeneous. They are VIII.2 and VIII.3. VIII.2 has 38 students while class VIII.3 has 39 students. Data collection instrument in this research is the understanding concept achievement test which consists of test items totaling 18 points multiple choice questions. Analysis of the data in this research is a descriptive analysis to see an overview of understanding concept result of students using the category of understanding concept. From the analysis of data showed: the average absorption of experiments class is 65.5 % and the average absorption of control class is 56 %. Thus, the results of experiments studying physics class higher than the control class. So it can conclude that learning using problem based learning strategies give good influential in understanding concept at material optical instruments in class VIII SMPN 26 Pekanbaru.Key Words : Problem Based Learning, Understanding Concept, Optical Instruments.